Ill. bij: "Het dappere Hollandsche leger in de troonrede en in de praktijk" door Hahn en Hermans - Hahn, Albert,
Ill. bij: "Het dappere Hollandsche leger in de troonrede en in de praktijk" door Hahn en Hermans.